2019
DOI: 10.1037/neu0000508
|View full text |Cite
|
Sign up to set email alerts
|

Semantic network function captured by word frequency in nondemented APOE ε4 carriers.

Abstract: Objective: Accurate identification of the earliest cognitive changes associated with Alzheimer's disease (AD) is critically needed. Item-level information within tests of category fluency, such as lexical frequency, harbors valuable information about the integrity of semantic networks affected early in AD.To determine the potential of lexical frequency as a cognitive marker of AD risk, we investigated whether lexical frequency of animal fluency output differentiated APOE ε4 carriers from noncarriers in a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…A promising avenue to exploit semantic fluency performance is to analyze item‐level data. Classically, analyses of cluster and switches have already been shown to add above and beyond total number of items in detecting MCI 40,41 and very mild AD, 42 and usage of psycholinguistic variables has demonstrated its value in distinguishing cognitively normal individuals at increased genetic risk of AD dementia by virtue of carrying an APOE e4 allele 43 . More research in this area should be encouraged, as the present study adds more evidence to the growing body of research on semantic breakdown in the very early stages of AD.…”
Section: Discussionmentioning
confidence: 99%
“…A promising avenue to exploit semantic fluency performance is to analyze item‐level data. Classically, analyses of cluster and switches have already been shown to add above and beyond total number of items in detecting MCI 40,41 and very mild AD, 42 and usage of psycholinguistic variables has demonstrated its value in distinguishing cognitively normal individuals at increased genetic risk of AD dementia by virtue of carrying an APOE e4 allele 43 . More research in this area should be encouraged, as the present study adds more evidence to the growing body of research on semantic breakdown in the very early stages of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Semantic memory efficiency, by contrast, allows for effective access to the storage of conceptual meanings, including the categories that concepts belong to. Semantic information is thought to be organized in a network, in which semantic activation spreads through related concepts (e.g., Vonk, Flores, et al, 2019 ). Thus, a task like Animal Fluency reflects the ability to quickly and accurately access concepts related to a category like animals .…”
Section: Discussionmentioning
confidence: 99%
“…To truly capture within-person trajectories of change over time, more follow-up measures are needed. Additionally, having only two measurement times prohibits consideration of practice effects that generally wear off after the second or third testing occasion ( Vonk, Arce Rentería, et al, 2019 ), which may bias estimates of change over time ( Vivot et al, 2016 ). Nonetheless, work by Mitrushina and Satz (1995) suggests that the ANT and BNT tasks may not be impacted by practice effects.…”
Section: Discussionmentioning
confidence: 99%
“…Episodic memory is the most characteristic cognitive function impaired in early Alzheimer’s disease ( Bäckman et al, 2001 ; Hodges, 1998 ). Additionally, a large body of research has demonstrated the role of subtle semantic decline in early stages of the disease or in individuals at high risk for Alzheimer’s disease (e.g., Chertkow et al, 2008 ; Papp et al, 2016 ; Vonk et al, 2019a ). While a decline in episodic memory is not only present in Alzheimer’s disease but to a lesser extent also in normal aging, several aspects of semantic cognition stay relatively intact with normal aging ( Horn and Cattell, 1966 , 1967 ; Park et al, 2002 ; Salthouse, 2010 ; Vonk et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%